Rise of the Indian Middle Class and Its Impact on the Labor Market - Andres Eggimann; Michael J. Kendzia (Institute of Labor Economics (IZA), 2022)
The world is changing its socio-economic landscape. By doing so, the phenomenon of a growing middle-class appears. Both household surveys and growth projections suggest that only about one-third of the global middle class is based in Asia. However, between 2009 and 2017, the global middle-class has increased from 1.8 billion to 3.5 billion, whereas 40 percent are located in Asia. The key contributors to this trend are China and India. Between 2011 and 2019, GDP per capita has surged by 66 percent in China and 53 percent in India. Forecasts by the OECD predict that between 2030 and 2035, India will overtake China in terms of middle-class population in absolute terms. Against this background, the article seeks to outline the implications that are associated with the rise of a growing middle class on India's labor market.
Keywords: E24; J21; J31; 330; middle class; India; labor market; employment; liberalization